ANALISIS MANAJEMEN PELAYANAN PADA CALON JAMA’AH HAJI DAN UMROH (PT. DAANISH MIKA SALSA TOURS AND TRAVEL) - Muhamad Bisri Mustofa; Siti Wuryan; Wahid Harsono (Institut Agama Islam Negeri Metro, 2021)
PT. DMS Tours and Travel is one of the institutions engaged in Hajj and Umrah services with a large number of pilgrims. Services provided by PT. Daanish Mika Salsa Tours and Travel, namely: Administrative services, including registration and document processing. Manasik guidance services, carried out 3 times with lecture, simulation and discussion methods. The transportation service provided is the transportation of pilgrims starting from the point of embarkation, while in Saudi Arabia, and returning to the place of debarkation from Indonesia. Accommodation services, PT. Daansh Mika Salsa Tours and Travel provides five-star hotel facilities, ranging from three, four and five stars according to the package chosen by the congregation. Consumption service, Each pilgrim will get food 3 times a day, namely in the morning, afternoon, and evening, and the tarvel provides additional Indonesian menus while at the hotel. Health services, carried out before departure and during worship.